2020
DOI: 10.3390/ijerph17238933
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment and Problematic Internet Use among Chinese Adolescents: The Moderating Role of Gender and Grit

Abstract: Problematic Internet use (PIU) is currently becoming a more serious public health concern, representing a deleterious effect on adolescent adaptive emotional and behavioral patterns. Given the prevalence of PIU and its deleterious impact on adolescents’ optimal functioning, it is valuable to investigate the risk and protective factors of PIU. Guided by a socio-ecological framework, the current study examines the associations of paternal attachment and maternal attachment with PIU among Chinese adolescents. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
(77 reference statements)
1
10
0
1
Order By: Relevance
“…This can happen because theoretically, the involvement of parents in their children's JAGC | 44 activities is inversely proportional to age. The older the children, the less involvement of their parents (Lan & Wang, 2020). This is allegedly causing parental involvement not to have much effect on the emergence of student PIU.…”
Section: Discussionmentioning
confidence: 99%
“…This can happen because theoretically, the involvement of parents in their children's JAGC | 44 activities is inversely proportional to age. The older the children, the less involvement of their parents (Lan & Wang, 2020). This is allegedly causing parental involvement not to have much effect on the emergence of student PIU.…”
Section: Discussionmentioning
confidence: 99%
“…Lei and Wu (2007) argued that securely attached adolescents were less prone to internet addiction than insecurely attached adolescents. In addition, in a study with an adolescent sample, it was found that paternal and maternal attachment security had buffering effects on problematic internet use (Lan & Wang, 2020). Further empirical evidence showed that secure attachment was a protective factor for PSMU both directly (e.g., Monacis et al, 2017;Musetti et al, 2022) and indirectly via its effects on personality characteristics (Rom & Alfasi, 2014;Yaakobi & Goldenberg, 2014).…”
Section: Effects Of Attachment On Psmu and Cyberbullyingmentioning
confidence: 97%
“…Unsichere Bindungsmuster sind zudem als Mediatoren in der Beziehung zwischen Bullying und Internetsucht beschrieben [30]. In einer Studie wurde die Entschlossenheit der Eltern als signifikanter Moderator identifiziert, wobei der Effekt dezente Geschlechtsunterschiede zeigte [21].…”
Section: Bindung Und Pathologischer Allgemeiner Internetkonsumunclassified